Insights from the AGNES Advanced Course on Climate Information Services: Tracking Knowledge Gains and Participant Engagement - Sagliocco, Livia; Grossi, Amanda; Ghosh, Aniruddha; Koech, Grace Jerotich; Gamoyo, Majambo Jarumani (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This report documents outcomes from the AGNES Advanced Course on Climate Information Services (CIS), a five-week online training jointly organized by AGNES, AICCRA, and the Alliance of Bioversity International & CIAT. Targeting over 150 professionals from across Africa, the course strengthened capacities in CIS generation, communication, and use for climate-resilient planning. Evaluation surveys revealed significant gains in conceptual understanding, sectoral application, and co-production methods, with 95% of participants satisfied and 90% intending to apply their learning. The report highlights lessons on enhancing practical engagement, regional balance, and sustainability, underscoring the course’s contribution to strengthening African leadership in climate-informed decision-making.